2016
DOI: 10.1089/cap.2015.0194
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin, Weight Gain, Disruptive Behavior, and Extrapyramidal Symptoms in Risperidone-Treated Youth

Abstract: Background: Iron deficiency disrupts dopaminergic signaling in rodents, resulting in cognitive deficits that may be reversed with psychostimulants. In humans, iron deficiency with or without anemia has similarly been found to cause neuropsychological and behavioral impairments. However, the clinical effects of low body iron stores in antipsychotic-treated children have not been examined. Methods: Medically healthy, 5-to 17-year-old boys treated with risperidone for at least 1 year were enrolled between Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
11
0
2
Order By: Relevance
“…In addition, impaired iron absorption may activate nutritional immunity in IECs and macrophages to sequestrate this biometal and deny it to pathogens, exacerbating hypoferremia and metabolic syndrome ( 133 , 134 ). On this point, a novel study in children and adolescents chronically treated with RSP found that iron status was inversely corelated with weight gain, contributing to dysmetabolic iron overload syndrome (DIOS) ( 135 ). This is significant as intracellular iron increases the risk of ROS generation that cannot be counteracted as Bacteroidetes depletion lowered IPA, a key gut antioxidant ( 98 , 136 , 137 ).…”
Section: Psychotropic Drugs As Antimicrobialsmentioning
confidence: 99%
“…In addition, impaired iron absorption may activate nutritional immunity in IECs and macrophages to sequestrate this biometal and deny it to pathogens, exacerbating hypoferremia and metabolic syndrome ( 133 , 134 ). On this point, a novel study in children and adolescents chronically treated with RSP found that iron status was inversely corelated with weight gain, contributing to dysmetabolic iron overload syndrome (DIOS) ( 135 ). This is significant as intracellular iron increases the risk of ROS generation that cannot be counteracted as Bacteroidetes depletion lowered IPA, a key gut antioxidant ( 98 , 136 , 137 ).…”
Section: Psychotropic Drugs As Antimicrobialsmentioning
confidence: 99%
“…Another factor that may be implicated in SGA-induced weight gain is the body’s intracellular storage of iron, as measured by ferritin [ 35 , 36 , 37 ]. Low ferritin, indicating low bodily iron stores, is possible independent of anemia as measured by low hemoglobin and hematocrit [ 37 ]. This could be particularly relevant in youth whose bodies are growing and require sufficient intracellular iron stores [ 37 ].…”
Section: Mechanisms Of Metabolic Syndromementioning
confidence: 99%
“…Low ferritin, indicating low bodily iron stores, is possible independent of anemia as measured by low hemoglobin and hematocrit [ 37 ]. This could be particularly relevant in youth whose bodies are growing and require sufficient intracellular iron stores [ 37 ]. Combining vertical growth with weight gain can deplete bodily iron stores more rapidly [ 37 ].…”
Section: Mechanisms Of Metabolic Syndromementioning
confidence: 99%
“…Both FGAs and SGAs can cause debilitating adverse drug reactions (ADR), which require the clinician weighing the need for treatment against the potential costs like ADRs as weight gain, metabolic syndrome, extrapyramidal symptoms (EPS), etc. [31,[36][37][38]. Among the SGAs, risperidone is the most extensively studied medication for the treatment of aggression and CD in children and adolescents.…”
Section: Impulsivity and Aggressionmentioning
confidence: 99%
“…A meta-analysis of the effect of risperidone in reducing symptoms of aggression including 875 subjects (mostly boys with a mean age of about 9 years) reported a large ES of 0.9 [33]. Other SGAs may be preferred if they cause less weight gain, which is the most relevant ADR of risperidone [38]. In the literature, there are indications that mood stabilizers can also reduce aggression associated with CD.…”
Section: Impulsivity and Aggressionmentioning
confidence: 99%